The Development of Animation-Based Learning Videos in Comparative Material for Class VII on Junior High School - Putri, Desti Tatian; Izzati, Nur (Tarbiyah : Jurnal Ilmiah Kependidikan, 2023)
This research is motivated by the need for more learning media development to support students' learning processes. This research aims to determine the validity of animation-based learning videos that will be developed in class VII Junior High School (Sekolah Menengah Pertama/SMP). In the implementation process, this research adopted the (R&D) method called Research and Development in foreign languages, referring to the 4D development model. To support the method used by researchers, a data collection tool was used as a validation questionnaire given to material expert validators, media expert validators, and language expert validators. From the validation results, information was obtained in the form of the feasibility of animation-based learning videos in comparative material for class VII SMP, which were developed in the very valid category, with a percentage of media expert assessment of 90%, material expert assessment of 91.4% and language expert assessment of 86%. Based on the overall data analysis results, the learning video media that will be developed is feasible and can be implemented in the learning process in class VII SMP.